Cognitive impairment in patients with schizophrenia: A comparative study from western Rajasthan - Nikita Dhaka; Arpit Koolwal; Aditi Agarwal; Ankit Awasthi; Ghanshyam Das Koolwal (Advances in Human Biology, 2020)
Introduction: Cognitive impairment is the core feature of schizophrenia (SCZ). The affected individuals exhibit wide-ranging deficits involving multiple domains of cognitive functioning. These deficits are associated with poor functional outcome and residual disability in patients. Substantial literature exists on cognition in SCZ; however, few studies have been carried out on this subject in India and in particular in Rajasthan. Objective: The objective was to evaluate cognitive functions in SCZ patients and to compare these with healthy controls. Materials and Methods: This cross-sectional study was conducted at the psychiatry department of a tertiary care institution on fifty schizophrenic patients and matched healthy controls who fulfilled the inclusion criteria. Diagnosis was made by DSM-V criteria, and symptom severity was determined by the Positive and Negative Symptom Scale. After seeking sociodemographic details, all participants were administered Postgraduate Institute Battery of Brain Dysfunction to assess their cognitive functioning. Data collected were subjected to suitable statistical analysis (mean, standard deviation and Chi-square test). Results: Majority of the schizophrenic patients (56%) were under 35 years of age, were males (70%), were from urban background (66%) and were married (70%). Schizophrenic patients performed poorly on all domains of cognitive functioning, including memory, performance and verbal intelligence and perceptuo-motor skills. Conclusion: The present study reiterated the previous findings of wide-spread, multidomain cognitive impairment in schizophrenic patients. The resultant cognitive profile has important implications for the aetiology and treatment of this major psychiatric disorder.